Hyphenation as a Reaction against the Fear (KULT_online, 2013)
The essays of the volume Arab American Literature and Culture investigate the various aspects of the identity and the expression of an "Arab-American culture" after the terrorist attacks of 9 September 2001. Drama, literature, movies, educational experiences, legal disquisitions, and news from the United States of today are contrastively analysed to illustrate the construction of an Arab-American Self as a reaction against the still-acting process of de-Americanization stemming from the policy of President Bush. Aesthetic and socio-political considerations make the volume an insightful work not only in the field of American Studies, but also in the domain of comparative literature and cultural transfer.